ANALISIS USAHATANI BLEWAH DI DESA DEMUNG KECAMATAN BESUKI ( Study Kasus Di Desa Demung Kec. Besuki Kab. Situbondo ) - Ifan DP Putra; Yohanes Nangameka (AGRIBIOS, 2015)
The research was determine the cantaloupe farm production, farm income cantaloupe, and cantaloupe farming efficiency in the Village of Demung District of Besuki. The hypothesis of this study is the production of a cantaloupe farm in the village of Demung high, cantaloupe farmer’s income in the village of Demung profitable, cantaloupe farm in the village of Demung efficient. The method used is descriptive method and survey. Descriptive method that is a picture or painting in a systematic, factual and accurate about the facts–facts as well as the relationship between the phenomena investigated. Survey method is to sampel determine the existing field and gave questionnaire to abtain information needed. The Population in this study there are 43 people who perform farm cantaloupe. And the sample is 20 cantaloupe farmers who farm in the village of Demung District of Besuki. The result showed that higher farm production, where the farm production cantaloupe reach averages 9.730 kg.. Cantaloupe farm income benefit, where in the farm income cantaloupe reach avareges Rp. 5.533.973. Cantaloupe farm in the Village of Demung efficient so deserves to be continued farming, where the averages level cantaloupe farming efficiency is 2,84. Based on the result of research conducted by researchers is the suggestion of farmers to continue farming with more developed because farming cantaloupe has a high prospect and try to cooperate with government agencies in order to provide new innovations, and the government should better supervise the issue price fluctuations cantaloupe so farmers can be assured in obtaining results from farming.